Muscle contraction induced arterial shear stress increases endothelial nitric oxide synthase phosphorylation in humans - Casey, Darren P.; Ueda, Kenichi; Wegman-Points, Lauren; Pierce, Gary L. (American journal of physiology. Heart and circulatory physiology, 2017)
We determined if local increases in brachial artery shear during repetitive muscle contractions induce changes in protein expression of endothelial nitric oxide synthase (eNOS) and/or phosphorylated (p-)eNOS at Ser 1177 , the primary activation site on eNOS, in endothelial cells (ECs) of humans. Seven young male subjects (25 ± 1 yr) performed 20 separate bouts (3 min each) of rhythmic forearm exercise at 20% of maximum over a 2-h period. Each bout of exercise was separated by 3 min of rest. An additional six male subjects (24 ± 1 yr) served as time controls (no exercise). ECs were freshly isolated from the brachial artery using sterile J-wires through an arterial catheter at baseline and again after the 2-h exercise or time control period. Expression of eNOS or p-eNOS Ser 1177 in ECs was determined via immunofluorescence. Brachial artery mean shear rate was elevated compared with baseline and the time control group throughout the 2-h exercise protocol ( P < 0.001). p-eNOS Ser 1177 expression was increased 57% in ECs in the exercise group [0.06 ± 0.01 vs. 0.10 ± 0.02 arbitrary units (au), P = 0.02] but not in the time control group (0.08 ± 0.01 vs. 0.07 ± 0.01 au, P = 0.72). In contrast, total eNOS expression did not change in either the exercise (0.13 ± 0.04 vs. 0.12 ± 0.03 au) or time control (0.12 ± 0.03 vs. 0.11 ± 0.03 au) group ( P > 0.05 for both). Our novel results suggest that elevations in brachial artery shear increase eNOS Ser 1177 phosphorylation in the absence of changes in total eNOS in ECs of young healthy male subjects, suggesting that this model is sufficient to alter posttranslational modification of eNOS activity in vivo in humans. NEW & NOTEWORTHY Elevations in brachial artery shear in response to forearm exercise increased endothelial nitric oxide synthase Ser 1177 phosphorylation in brachial artery endothelial cells of healthy humans. Our present study provides the first evidence in humans that muscle contraction-induced increases in conduit arterial shear lead to in vivo posttranslational modification of endothelial nitric oxide synthase activity in endothelial cells.